A Constitutional Review of Indonesia’s Marriage Law: Legal Reconstruction and Human Rights Considerations in Law No. 1 of 1974 - Nuruddin, Nuruddin; Jannah, Aisyah Wardatul (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 13 No 4 (2024), 2025)
Law No. 1 of 1974 represents the unification of national laws in the field of marriage, deriving from Islamic law, civil law, and customary law. As society has progressed in the era of modernization and digitalization, this law has presented numerous legal issues, underscoring the need for legal reform to address legal voids and conflicts. Over its 50-year history, at least seven judicial reviews have been initiated, challenging provisions that conflict with the 1945 Constitution of the Republic of Indonesia (UUD NRI 1945), particularly those that are inconsistent with principles of justice and human rights for all citizens. This study utilizes normative (doctrinal) legal research methods, incorporating three approaches: statutory, comparative law, and analytical methods. The analysis highlights the necessity of reconstructing Law No. 1 of 1974 on Marriage to ensure it aligns with principles of justice and human rights, focusing especially on Article 2(1) (regarding interfaith marriages), Article 7 (marriageable age), Article 43(1) (status of children born outside of lawful marriage), Article 57 (mixed marriages), and provisions related to child rights post-divorce.